2009
DOI: 10.1002/ijc.24563
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sp1 leads to p53‐dependent apoptosis in cancer cells

Abstract: Numerous studies have documented that Sp1 expression level were elevated in various human cancers. However, the promoters of many pro-apoptotic genes have been found to contain the Sp1 binding elements and are activated by Sp1 overexpression. To better understand the role and the mechanism of increased Sp1 levels on apoptosis, we used adenovirus to ectopically express GFP-Sp1 protein in various cancer cell lines. First, in HeLa and A549 cells, we found that Sp1 overexpression suppressed the cell growth and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 40 publications
2
63
0
1
Order By: Relevance
“…High levels of Sp1 in highly invasive lung adenocarcinoma cells were associated with increased E-cadherin expression and metastasis inhibition [55] . In addition, Chuang et al found that Sp1 cooperates with p53 to induce apoptosis in a variety of cancer cells, including lung adenocarcinoma, cervical adenocarcinoma, breast carcinoma, colon carcinoma and glioma cells [56] . Recently, Zhang et al reported that aberrant overexpression of Sp1 was observed in advanced tumor stages in NPC, and knockdown of Sp1 by siRNA inhibited proliferation and led to cell cycle arrest in NPC cells [21] , suggesting the potential of Sp1 as a therapeutic target in NPC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of Sp1 in highly invasive lung adenocarcinoma cells were associated with increased E-cadherin expression and metastasis inhibition [55] . In addition, Chuang et al found that Sp1 cooperates with p53 to induce apoptosis in a variety of cancer cells, including lung adenocarcinoma, cervical adenocarcinoma, breast carcinoma, colon carcinoma and glioma cells [56] . Recently, Zhang et al reported that aberrant overexpression of Sp1 was observed in advanced tumor stages in NPC, and knockdown of Sp1 by siRNA inhibited proliferation and led to cell cycle arrest in NPC cells [21] , suggesting the potential of Sp1 as a therapeutic target in NPC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have established that AATF genome encoded miR-2909 not only requires nuclear RelA translocation for its expression but also this microRNA regulates gene expression through repression of KLF4 gene expression resulting in the up-regulation of SP1 gene expression [7,8]. At this stage, it is pertinent to note that: a) SP1 has been shown to induce genes coding for AATF, CCL5 and p53 [13][14][15]; b) p53 gene expression is also induced by CCL5 and AATF-dependent translocation of RelA to p53 gene promoter [6,16]; c) KLF4 has been shown to induce IL-17 gene expression [12] and p53 binds RelA to block its translocation either to nucleus or mitochondria [4]; d) KLF4 is known to repress Bmi-1 gene which is known to degrade the p53 protein [17,18]. The results reported here together with above-mentioned findings in the literature, led us to the mechanism which reveals as to how AATF RNome can regulate UCP2 gene in a cyclic fashion (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…2A) and KLF4 has been shown to induce IL-17 expression [12] whereas SP1 has been shown to induce genes coding for CCL5, AATF and p53 [13][14][15]. Both ectopic miR-2909 expression and its down-regulation with antagomiR-2909 resulted in the corresponding modulation of genes coding for IL-17 and UCP2 (Fig.…”
Section: Mir-2909 Rnomics Regulated Genesmentioning
confidence: 89%
“…Sp1 is a transcription factor that either enhance or repress the activity of promoters of genes involved in differentiation, cell cycle progression and oncogenesis (34). In comparison to normal tissues or cells, Sp1 level is greater in breast carcinomas, thyroid cancer, hepatocellular carcinomas, pancreatic cancer, colorectal cancer, gastric cancer and lung cancer (34)(35)(36)(37). Sp1 is also overexpressed in ovarian cancer (38) and plays an important role in the process of cancer.…”
Section: Discussionmentioning
confidence: 99%